The challenge of sustainability in agricultural systems volume 2 - Tanda, Maria Giovanna; Chiapponi, Luca (Lecture Notes in Networks and Systems, 2021)
This book brings together segmental knowledge and creates new insights on the sustainability of agricultural systems, critically analyzing not only individual system components, but also focusing on interactions between them and external environments. This book is primarily devoted to (1) agricultural agribusiness, (2) policies and institutions, and (3) farming systems. The compelling collection of chapters presents critical, comparative, and balanced perspectives on what changes are needed to achieve and maintain sustainability in agricultural systems, actively leading to new ways of thinking about these complex issues. The research presented relies on an array of methods developed within complex systems science, addresses the existing gaps in the scholarship, and uses original data collected on the development of agricultural systems. Finally, the authors provide robust conclusions and recommendations for both scholars and practitioners in the field of studying, constructing, and maintaining sustainable agricultural systems. The special focus of the book is on technologies, policies, and management systems enabling sustainable agricultural development. A rich collection of practical cases could be used to move from theories to reality. The book appeals to both academics and professionals working in the field.